New insights into the cold tolerance of upland switchgrass by integrating a haplotype-resolved genome and multi-omics analysis - Bingchao Wu; Dan Luo; Yuesen Yue; Haidong Yan; Min He; Xixi Ma; Bingyu Zhao; Bin Xu; Jie Zhu; Jing Wang; Jiyuan Jia; Min Sun; et al. (Genome Biology)
Abstract Background Switchgrass (Panicum virgatum L.) is a bioenergy and forage crop. Upland switchgrass exhibits superior cold tolerance compared to the lowland ecotype, but the underlying molecular mechanisms remain unclear. Results Here, we present a high-quality haplotype-resolved genome of the upland ecotype “Jingji31.” We then conduct multi-omics analysis to explore the mechanism underlying its cold tolerance. By comparative transcriptome analysis of the upland and lowland ecotypes, we identify many genes with ecotype-specific differential expression, particularly members of the cold-responsive (COR) gene family, under cold stress. Notably, AFB1, ATL80, HOS10, and STRS2 gene families show opposite expression changes between the two ecotypes. Based on the haplotype-resolved genome of “Jingji31,” we detect more cold-induced allele-specific expression genes in the upland ecotype than in the lowland ecotype, and these genes are significantly enriched in the COR gene family. By genome-wide association study, we detect an association signal related to the overwintering rate, which overlaps with a selective sweep region containing a cytochrome P450 gene highly expressed under cold stress. Heterologous overexpression of this gene in rice alleviates leaf chlorosis and wilting under cold stress. We also verify that expression of this gene is suppressed by a structural variation in the promoter region. Conclusions Based on the high-quality haplotype-resolved genome and multi-omics analysis of upland switchgrass, we characterize candidate genes responsible for cold tolerance. This study advances our understanding of plant cold tolerance, which provides crop breeding for improved cold tolerance.